2006
DOI: 10.1016/j.virol.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of vaccines based on flaviviruses defective in replication

Abstract: To develop new vaccine candidates for flavivirus infections, we have engineered two flaviviruses, yellow fever virus (YFV) and West Nile virus (WNV), that are deficient in replication. These defective pseudoinfectious viruses (PIVs) lack a functional copy of the capsid (C) gene in their genomes and are incapable of causing spreading infection upon infection of cells both in vivo and in vitro. However, they produce extracellular E protein in form of secreted subviral particles (SVPs) that are known to be an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 46 publications
5
85
1
1
Order By: Relevance
“…Thus, the balance between IFN production that blocks attenuated vaccine virus spread and the need to attenuate viral replication to prevent disease could help to explain why live attenuated vaccines for some flaviviruses have been so difficult to produce. On the other hand, the autoadjuvant effect would have a less severe effect on the immune responses engendered by VLP or VLP-like vaccines, such as our recently reported pseudo-infectious flavivirus vaccines (30). Interestingly, recent reports on VLPs from alphaviruses have also reported that they can stimulate strong immune responses, likely through a similar mechanism of activation (46).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the balance between IFN production that blocks attenuated vaccine virus spread and the need to attenuate viral replication to prevent disease could help to explain why live attenuated vaccines for some flaviviruses have been so difficult to produce. On the other hand, the autoadjuvant effect would have a less severe effect on the immune responses engendered by VLP or VLP-like vaccines, such as our recently reported pseudo-infectious flavivirus vaccines (30). Interestingly, recent reports on VLPs from alphaviruses have also reported that they can stimulate strong immune responses, likely through a similar mechanism of activation (46).…”
Section: Discussionmentioning
confidence: 90%
“…Inactivated viral vaccines are safer than live attenuated viruses but are more expensive, less efficient, and require large-scale production of the virus (10). Subviral particles or virus-like particles (VLPs), produced either in vitro or in vivo, represent an important alternative to inactivated vaccines (13)(14)(15). In contrast to subunit vaccines, they closely mimic the antigenic structure of natural virions and induce a more natural spectrum of neutralizing and protective antibodies but transmit no viral genetic material and are incapable of developing a spreading infection or viremia.…”
mentioning
confidence: 99%
“…The approach is based on replication-defective flavivirus mutants produced in helper cells (14)(15)(16)(17). RepliVax constructs are engineered to have a deletion, removing most of the capsid protein C gene.…”
mentioning
confidence: 99%
“…In normal cells, both in vitro and in vivo, they undergo a single round of replication only, and cannot spread to surrounding cells. Infected cells efficiently secrete empty viruslike particles (VLP, the product of the prM-E genes) devoid of the nucleocapsid (14) which represent the active immunogen. Cryoelectron microscopy of TBE VLPs has shown that they are smaller than complete virions but have similar architecture of the envelope (18) and therefore should be highly immunogenic.…”
mentioning
confidence: 99%